Myeloid-related protein-8/14 facilitates bacterial growth during pneumococcal pneumonia. Issue 11 (1st September 2014) - Achouiti, Ahmed; Vogl, Thomas; Endeman, Henrik; Mortensen, Brittany L; Laterre, Pierre-Francois; Wittebole, Xavier; van Zoelen, Marieke A D; Zhang, Yaofang; Hoogerwerf, Jacobien J; Florquin, Sandrine; Schultz, Marcus J; Grutters, Jan C; et al.
Abstract : Background: Streptococcus pneumoniae is the most commonly identified pathogen in community-acquired pneumonia (CAP). Myeloid-related protein (MRP) 8/14 is a major component of neutrophils that is released upon infection or injury. MRP8/14 is essential for protective immunity during infection by a variety of micro-organisms through its capacity to chelate manganese and zinc. Here, we aimed to determine the role of MRP8/14 in pneumococcal pneumonia. Methods: MRP8/14 was determined in bronchoalveolar lavage fluid (BALF) and serum of CAP patients, in lung tissue of patients who had succumbed to pneumococcal pneumonia, and in BALF of healthy subjects challenged with lipoteichoic acid (a component of the gram-positive bacterial cell wall) via the airways. Pneumonia was induced in MRP14 deficient and normal wildtype mice. The effect of MRP8/14 on S. pneumoniae growth was studied in vitro. Results: CAP patients displayed high MRP8/14 levels in BALF, lung tissue and serum. Healthy subjects challenged with lipoteichoic acid demonstrated elevated MRP8/14 in BALF. Likewise, mice with pneumococcal pneumonia had high MRP8/14 levels in lungs and the circulation. MRP14 deficiency, however, was associated with reduced bacterial growth and lethality, in the absence of notable effects on the inflammatory response. High zinc levels strongly inhibited growth of S. pneumoniae in vitro, which was partially reversed by MRP8/14. Conclusions: In sharp contrast to its previously reported host-protective role in several infections, the present results reveal that in a model of CAP, MRP8/14 is misused by S. pneumoniae, facilitating bacterial growth by attenuating zinc toxicity toward the pathogen.